The characterization of undoped SnOx thin film grown by reactive ion-assisted deposition - Choi, WK; Cho, JS; Song, SK; Jung, HJ; Koh, SK; Yoon, KH; Lee, CM; Sung, MC; Jeong, K (ELSEVIER SCIENCE SA LAUSANNE, 1997)
Undoped oxygen-deficient SnOx films were deposited on Si (100) and BK7 glass substrates by the reactive ion-assisted deposition technique. The average impinging energy (E-a) of the oxygen ion on depositing a Sn atom, a relative arrival ratio of ion to atom (Gamma), was varied from Gamma=0.025 (E-a=25 eV atom(-1)) to Gamma=0.1 (E-a=100 eV atom(-1)) by controlling the discharge voltage at a fixed ion-beam potential of 500 V. Crystalline structures of as-deposited SnOx films appeared to be amorphous for all E-a values. In order to precisely examine the dependence of oxidation from SnO to SnO2 on initial oxygen content and annealing temperature, as-deposited SnOx films containing initially different oxygen contents were annealed at 400 similar to 500 degrees C in a low vacuum (similar to 5x10(-3) Torr) for 1 h to remove the external oxygen diffusion effect during the annealing process. The heat-treated SnOx films at 400 degrees C showed polycrystalline SnO structure until E-a=50 eV atom(-1) and were still amorphous over E-a=75 eV atom(-1). But after annealing over 500 degrees C those films over E-a=75 eV atom(-1) exhibited diffraction peaks at (110), (101), and (211), characteristic of polycrystalline SnO2. Scanning electron microscopy (SEM) micrographs for the as-deposited SnOx films show gains as small as a few tens of angstroms in size, but those after 500 degrees C annealing reveals that the number of granular grain became larger in cross-sectional SEM and the grain grew to 300 Angstrom at E-a=100 eV atom(-1). For as-deposited films, the root-mean-square of surface roughness (sigma) slightly increased from 9 to 25 Angstrom as E-a was increased, but conversely it reduced from 36 Angstrom to 13 Angstrom after annealing. From quantitative Auger electron spectroscopy, it was observed that characteristic transitional Auger peaks of Sn MNN shift to lower kinetic energy by as much as 3.8 similar to 4.2+/-0.02 eV in the case of the SnO films and 4.8 similar to 5.2+/-0.02 eV for SnO2 films, respectively. with respect to that of Sn metal (Sn-0). Based on the valence band spectra taken by using He I angle-resolved ultraviolet photoelectron spectroscopy (angle-resolved UPS), two different phases of polycrystalline SnO and SnO2 firms were clearly distinguished. The binding energy difference between the first peaks derived from SnO and SnO2 films in angle-resolved UPS spectra below the Fermi level was 1.6 eV. This value is very close to the value obtained from clean SnO and SnO2 samples by previous valence-band XPS spectra. As-deposited and annealed films showed optical transmittance as high as more than 80% grown at higher than E-a=50 eV atom(-1) in the visible wavelength and refractive index close to the bulk SnO,value for the film deposited at E-a=100 eV atom(-1) after annealing. (C) 1997 Elsevier Science S.A.
Keywords: TIN OXIDE-FILMS; OPTICAL-PROPERTIES; OXYGEN VACANCIES; ELECTRON; PHOTOEMISSION; OXIDATION; SURFACE; STATES